The Role of Brand Image in Mediating the Influence of Social Media Marketing and Product Quality on Purchase Decision Uniqlo in Indonesia - Akbari, Rizki Zulfi; Wendy; Listiana, Erna; Hasanudin; Fauzan, Rizky (Yayasan Ilomata, 2024)
Based on the implication that brand image serves as a mediator between social media marketing and purchase decisions, Uniqlo can maximize their social media approach. This could be improved online communication, marketing that tell stories, or the application of unique social media platform characteristics that improve brand perception. This study aims to investigate the relative influence of social media marketing, product quality, and brand image on purchasing decisions. The research design chosen was causal research with purposive sampling technique. A questionnaire given to participants who met the requirements was used in this study. In this survey, a 5-point Likert scale was used (1 meaning strongly disagree and 5 meaning strongly agree). The large sample collected and surveyed in this research consisted of 200 respondents. The samples involved were Uniqlo consumers based in Indonesia. Structural Equation Modeling (SEM) with the AMOS 24 statistical tool will be used to construct and assess the measurement model and structural model of the research design. This research has shown how social media marketing, product quality, and brand image all have a big relationship on consumers' purchase decisions to buy, both on direct influence or indirect influence mediated by brand image.